Effects of biochar and vermicompost on growth and economic benefits of continuous cropping pepper at karst yellow soil region in Southwest China - Zhang, Meng; Liu, Yanling; Wei, Quanquan; Liu, Lingling; Gu, Xiaofeng; Gou, Jiulan; Wang, Ming (Frontiers in Plant Science, 2023)
Recently, biochar (B) and vermicompost (V) have been widely used as amendments to improve crop productivity and soil quality. However, the ameliorative effects of biochar and vermicompost on the continuous cropping of pepper under open-air conditions, particularly in the karst areas of southwestern China, remain unclear. A field experiment was conducted to study the effects of biochar and vermicompost application, alone or in combination, on the yield, quality, nutrient accumulation, fertilizer utilization, and economic benefits of continuous pepper cropping from 2021 to 2022. The experiment included six treatments: CK (no fertilizer), TF (traditional fertilization of local farmers), TFB (TF combined with biochar of 3000 kg·ha-1), TFV (TF combined with vermicompost of 3000 kg·ha-1), TFBV1 (TF combined with biochar of 1500 kg·ha-1 and vermicompost of 1500 kg·ha-1), and TFBV2 (TF combined with biochar of 3000 kg·ha-1 and vermicompost of 3000 kg·ha-1). Compared with the TF treatment, biochar and vermicompost application alone or in combination increased the yield of fresh pod pepper by 24.38–50.03% and 31.61–88.92% in 2021 and 2022, respectively, whereas the yield of dry pod pepper increased by 14.69–40.63% and 21.44–73.29% in 2021 and 2022, respectively. The application of biochar and vermicompost reduced the nitrate content and increased the vitamin C (VC) and soluble sugar content of the fruits, which is beneficial for improving their quality. Biochar and vermicompost application alone or in combination not only increased nutrient uptake but also significantly improved agronomic efficiency (AE) and recovery efficiency (RE). In addition, although the application of biochar or vermicompost increased production costs, the increase in yield improved net income (ranging from 0.77 to 22.34% in 2021 and 8.82 to 59.96% in 2022), particularly in the TFBV2 treatment. In conclusion, the use of biochar and vermicompost amendments had a positive effect on the productivity and economic benefits of continuous pepper cropping, and the co-application of biochar and vermicompost could be an effective nutrient management strategy for the continuous cropping of pepper in the karst mountain areas of southwest China.